INTENSITAS PENDIDIKAN LINGKUNGAN KELUARGA DAN PENGELOLAAN KEUANGAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN EKONOMI UNTAN - zamzami, zamzami; Asriati, Nuraini; Syamsuri, Syamsuri; Syahrudin, Husni; Budiman, Jumardi (STKIP Persada Khatulistiwa Sintang, 2023)
With increasing competition in the job market, every individual must be able to create jobs through entrepreneurship. Therefore, a separate corporate strategy is needed to succeed in entrepreneurship. This research aims to determine the magnitude of the influence of the intensity of Economic Education in the family environment on interest in entrepreneurship through financial management of FKIP Untan students. The research method used is path analysis with a quantitative form. The data sources obtained were economic education students from the 2019, 2020 and 2021 classes for Regular A and PPAPK classes and the data was obtained from the results of distributing questionnaires. The sample used was 60 economic education students from the classes of 2019, 2020 and 2021. The results of this research show that: The intensity of economic education in the family environment has a significant influence on interest in entrepreneurship of 0.616 with a significance level of 0.000 < 0.05; Financial management has a significant influence on the interest in entrepreneurship of 0.724 with a significant level of 0.000 <0.05; The intensity of economic education in the family environment and financial management has an indirect influence on interest in entrepreneurship of 0.303 with a tcount of 2.767 > ttable of 2.000.